PELAKSANAAN FUNGSI PERPUSTAKAAN DAN PENGARAUHNYA TERHADAP MINAT BACA PESERTA DIDIK DI SMP NEGERI 1 PANGKALAN KERINCI - Yuliani, Rani; Gimin, Gimin; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Extracurricular The research based on the observation was done by the researcher at SMP Negeri 1 Pangkalan Kerinci. It showed lack of students’ interest on the library conditions it causes the problem by students to increase their knowledge. The formally, the function of the library is aimed to education. The specifically, the function of the library is to increase students’ interes in reading, because of that the library is very important for students. This research was aimed to know the implementation of the library function and the influence on students’ interest at SMP Negeri 1 Pangkalan kerinci Pelalawan Regency. The sampel of this research was 40 students. The instrument of data collection by using observation, interview, questionnaire and documentation. This research is a quantitative descriptive analaysis. The implementation of the library functions and the influences on student interest at smp negeri 1 pangkalan kerinci are in good level. There is a significant influence between the implementation of the library function on reading students’ interest at SMP Negeri 1 Pangkalan Kerinci are in good level. So the hypothesis is the research was acceptex. The result found that the cooficient of determination (Rsquere) os 0458. Its mean thet the influence of independent variabel (implementation of the library function) on dependent variabel (students’ interest of reading) is 67.7%Key Words: Implementation Of The Library Funcions, Influence, Reading